FORMULASI REGULASI UPAH MINIMUM YANG RESPONSIF TERHADAP KEBUTUHAN PEKERJA/BURUH (Studi Implementasi Regulasi Upah Minimum Di Kabupaten Malang) - Dian Dharu Rohmadhoni (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
Abstract The writing of this research journal was motivated by the problem of workers / laborers remuneration which led to the turmoil and rejection of the minimum wage regulations by workers / laborers. The mandate of Article 88 of Law Number 13 Year 2003 on Employment that every worker / laborer is entitled to the income that meets a decent livelihood for humanity. Problems in this paper were formulated in three formulation of the problem. First, why the formulation of the regulation of generated minimum wage is not responsif to the needs of workers/laborers. Second, what is the implications of the minimum wage regulation that is not responsif to the needs of workers/laborers. Third, How is the formulation of Minimum Wage regulation to be responsif to the needs of workers/laborers. The writing of this journal was using juridical empirical research methods. The cause of formulations of unresponsif generated Minimum Wages regulation was a component of the Good Living Needs (KHL) and the selection of determined quality or brand did not meet the needs of workers/laborers, the mechanism in the determination of Minimum Wages was run with unbalance because local governments should consider the investment and development factor of the region, and there were no penalties for companies that violate the specified local Minimum Wages. The unresponsif Minimum Wages Regulation to the needs of workers / laborers were implications for workers / laborers who could not fulfill their needs adequately, the company could not obtain the best productivity and for local government, there were an upheaval employment becomes a bad score for conduciveness of Industrial Relations in the local area , the formulation of responsif minimum wages regulation to the needs of workers/laborers was that the government should be able to act as a counterweight to the interests of workers/laborers and entrepreneurs, decision-making mechanism in the Wage Council was conducted by deliberation involving academics as a neutral party, the component of the Good Living Needs (KHL) was adjusted to the needs of workers/laborers today, explicitly regulation for employers who violate the designation of Work Minimum Wage. Key words: regulation, minimum wage, responsif Abstrak Penulisan jurnal penelitian ini dilatarbelakangi oleh permasalahan pengupahan yang menimbulkan gejolak dan penolakan atas regulasi upah minimum oleh pekerja/buruh. Amanat pasal 88 Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan bahwa setiap pekerja/buruh berhak memperoleh penghasilan yang memenuhi penghidupan yang layak bagi kemanusiaan. Permasalahan dalam tulisan ini dirumuskan, Pertama, mengapa formulasi regulasi upah minimum yang dihasilkan tidak responsif terhadap kebutuhan pekerja/buruh. Kedua, Bagaimana implikasi regulasi Upah Minimum yang tidak responsif terhadap kebutuhan pekerja/buruh. Ketiga, Bagaimana formulasi regulasi Upah Minimum yang responsif terhadap kebutuhan pekerja/buruh. Penulisan jurnal ini menggunakan metode penelitian yuridis empiris. Tujuan jurnal ini menjelaskan dan menganalisis tentang penyebab dan implikasi hukum regulasi upah minimum yang tidak responsif dan formulasi regulasi upah minimum yang responsif terhadap kebutuhan pekerja/buruh. Penyebab formulasi regulasi upah minimum tidak responsif adalah komponen dan pemilihan kualitas KHL yang ditetapkan tidak memenuhi kebutuhan pekerja/buruh, mekanisme penetapan upah minimum yang dilakukan berjalan secara tidak berimbang karena pemerintah daerah harus mempertimbangkan faktor investasi dan perkembangan daerah, dan tidak ada sanksi bagi perusahaan yang melanggar peruntukkan Upah Minimum Kabupaten. Implikasi upah minimum yang tidak responsif adalah kebutuhan pekerja/buruh tidak terpenuhi secara layak, produktivitas perusahaan tidak baik, dan bagi pemerintah daerah terjadinya gejolak ketenagakerjaan yang menjadi nilai buruk bagi kondusivitas Hubungan Industrial di daerah. Formulasi regulasi upah minimum responsif terhadap kebutuhan pekerja/buruh apabila pemerintah berperan sebagai penyeimbang kepentingan pekerja/buruh dan pengusaha, mekanisme pengambilan keputusan dalam Dewan Pengupahan dilakukan secara musyawarah dengan melibatkan akademisi sebagai pihak netral, komponen KHL disesuaikan dengan kebutuhan pekerja/buruh saat ini, dan sanksi bagi pengusaha pelanggar ketentuan UMK. Â  Kata kunci: regulasi, upah minimum, responsif